Do Processing Times Affect the Distribution of Asylum Seekers across Europe? - Simone Bertoli; Herbert Brücker; Jesús Fernández-Huertas Moraga (Institute of Labor Economics (IZA), 2020)
More than 3 million asylum seekers arrived into Europe between 2014 and 2016, and we analyze the role of destination-specific policy measures in shaping their location choices. We bring to the data a gravity equation that reflects the uncertainty that asylum seekers face, concerning the chances of obtaining refugee protection, the processing time and the risk of repatriation. These factors shaped the distribution of asylum seekers, and produced heterogeneous effects across different origin countries. German efforts to expand their processing capacity produced a significant increase in applications from origins with high recognition rates, which were mostly diverted away from Sweden.
Keywords: F22; K37; 330; refugees; recognition rate; processing time; gravity equations; migration